Effect of therapeutic play on postoperative pain of hospitalized school age children in pediatric surgical ward - Baratee, Fatemeh; Dabirian, Akram; Yoldashkhan, Mehryar; Zaree, Farid; Rasouli, Maryam (Advances in Nursing & Midwifery, 2012)
Effect of therapeutic play on postoperative pain of hospitalized school age children in pediatric surgical ward Baratee F1 (MSM); Dabirian A2* (MSM); Yoldashkhan M3 (MD); Zaree F4 (PhD); Rasouli M 1. Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran 2. Lecturer, Dept. of Pediatric, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran 3. Lecturer, Dept. of Anestisiology, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran 4. Assistant Professor, Dept. of Biostatistics, Faculty of Paramedical, Shahid Beheshti University of Medical Sciences, Tehran, Iran 5. Assistant Professor, Dept. of pediatric, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran Abstract Background and aim A majority of children experience moderate to severe postoperative pain. To ensure adequate pain relief in pediatric patients, non pharmacological techniques are needed for use in conjunction with pain medication. The aim of this study was to determine the effect of therapeutic play on postoperative pain of hospitalized school age children in surgical ward of Sheikh’s Pediatric Hospital affiliated to Mashhad Medical University in 2009-2010. Materials and methods In this randomized clinical trial, 40 hospitalized children in surgical ward between the age of 8 and 12 years old were selected and randomly assigned to the experimental group who participated in a session of therapeutic play that lasted between 30 and 45 minutes whereas those in the control group received routine care. Data collection tools included demographic questionnaire and Objective Numeric Pain Scales. The intensity of pain was assessed before (Phase1), immediately after (Phase2), and 15 minutes after (Phase3) intervention or routine care. The validity of ’Objective Pain Scales’ and ‘Numeric Pain Scales’ were determined by concurrent validity (0/89) and between ‘Objective Pain Scales’ and ‘Face pain Scale’ (0/95). Reliability of ‘Objective Pain Scales’ was measured by inter -rater reliability (0/95). Data were analyzed by SPSS v16. Findings The results showed that children in the experimental group reported having significantly less pain (p<0/001) than the control group based on a comparison pain scores in Phases 1 and 2 and 3. Conclusion The findings of this study have shown the positive effect of therapeutic play on postoperative pain of hospitalized school age children. Keywords: Postoperative pain, Therapeutic play, School age children. Corresponding Author: Akram Dabirian, Dept. of Pediatric, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: a.dabirian@yahoo.com